Antioxidant Activities of Triterpenoids and Steroid from the Roots of Millettia utilis Dunn - Ruksilp, Thanatip; Wongpriaw, Napatsorn; Thammasom, Thitinan; Srichana, Niramon; Isaro, Wira (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 3 (2022): July-September 2022DO - 10.14456/nujst.2022.25, 2021)
Two triterpenoids, oleanolic acid acetate ( 1 ), corosolic acid ( 2 ) and one steroid, stigmasterol ( 3 ) were isolated from dichloromethane  crude extract in the roots of Millettia utilis Dunn. The structures of all isolated compounds were elucidated by spectroscopic methods  and compared with previous literatures. The antioxidant activities using DPPH and ABTS assays of three isolated compounds were tested. Oleanolic acid acetate ( 1 ), corosolic acid ( 2 )  were revealed moderate and stigmasterol ( 3 ) was weak activity against DPPH and ABTS assays. Keywords: Millettia utilis Dunn., steroids, triterpenoids, DPPH, ABTS